2002
DOI: 10.1046/j.1365-2230.2002.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Fixed drug eruption following metronidazole therapy and the use of topical provocation testing in diagnosis

Abstract: Fixed drug eruption is characterized by recurrent well-defined lesions appearing in the same location each time the drug responsible is taken. A number of agents have been implicated. Metronidazole, a nitroimidazole agent widely used for its antibacterial and antiprotozoal activity, has been reported only rarely as the causative agent. We describe a patient with FDE due to metronidazole in whom we were able to induce the clinical and histological features of FDE by topical provocation testing. In agreement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…This may be due to localized changes in vascularity and vascular permeability or to the presence of a chronic inflammatory infiltrate including memory T cells. Comparisons may be drawn with a fixed drug eruption, where an increase in expression of intracellular adhesion molecule‐1 on lesional keratinocytes, following first exposure to the drug, is thought to provide a localized‐initiating stimulus for activation of disease‐associated epidermal T cells on subsequent exposure (4). In our case, reactivation of eczema as the result of patch testing may have acted as the trigger.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to localized changes in vascularity and vascular permeability or to the presence of a chronic inflammatory infiltrate including memory T cells. Comparisons may be drawn with a fixed drug eruption, where an increase in expression of intracellular adhesion molecule‐1 on lesional keratinocytes, following first exposure to the drug, is thought to provide a localized‐initiating stimulus for activation of disease‐associated epidermal T cells on subsequent exposure (4). In our case, reactivation of eczema as the result of patch testing may have acted as the trigger.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is a diagnosis of exclusion based on persistent discomfort, most often described as burning pain, that is present without objective cutaneous findings and no identifiable infectious, inflammatory, neoplastic, or neurologic cause. 1 It is a diagnosis of exclusion based on persistent discomfort, most often described as burning pain, that is present without objective cutaneous findings and no identifiable infectious, inflammatory, neoplastic, or neurologic cause.…”
Section: Successful Treatment Of Vulvodynia With Botulinum Toxin Amentioning
confidence: 99%
“…1 Localized provoked vulvodynia is the most common subtype and is usually triggered by sexual activity or tampon insertion. Bowen et al 3 found that 61% of patients referred to a tertiary vulvovaginal clinic for chronic vulvar pain had a clinically relevant dermatologic condition; therefore, dermatologists may play a primary role in the care of these patients.…”
Section: Report Of a Casementioning
confidence: 99%
“…Sixteen cases of drug eruption caused by TH were reported; 1 10 of these cases involved children and were all FDE. Patch testing on the site of previously affected skin is safe and useful for confirming the drug responsible for the FDE 2,3 . However, in the child cases above of FDE, only one patient was positive in patch test, whereas the oral challenge test was required for diagnosis in the remaining nine cases.…”
mentioning
confidence: 99%
“…However, in the child cases above of FDE, only one patient was positive in patch test, whereas the oral challenge test was required for diagnosis in the remaining nine cases. Generally, negative results for the patch tests were attributed to inadequate transepidermal absorption 2,3 or to lack of metabolic modification of the drugs in the gastrointestinal tract or liver 4 . Therefore, in the event of a negative LST result or a patch test for a suspected case of FDE by TH, an oral challenge test should be performed to avoid subsequent prescription and resulting in systemic involvement, such as Stevens–Johnson syndrome 5 …”
mentioning
confidence: 99%